Influence of t-PA and u-PA on Adipose Tissue Development in a Murine Model of Diet-Induced Obesity - Morange, P.E.; Bastelica, D.; Bonzi, M.F.; Van Hoef, B.; Collen, D.; Juhan-Vague, I.; Lijnen, H.R. (Thrombosis and Haemostasis, 2002)
To investigate the potential role of tissue-type plasminogen activator (t-PA) or urokinase-type plasminogen activator (u-PA) in development of adipose tissue, we have used a nutritionally induced obesity model in t-PA (t-PA−/−) and u-PA (u-PA−/−) deficient mice. Five week old male wild-type (WT), t-PA−/− or u-PA−/− mice (n = 9 to 16) were fed a high fat diet (HFD, 42% fat). After 16 weeks of HFD, the body weight of t-PA−/− mice was significantly higher than that of WT mice (48 ± 1.1 g vs. 39 ± 2.2 g, p = 0.004). The total weight of the isolated subcutaneous (sc) fat deposit was higher in t-PA−/− than in WT mice (2.4 ± 0.22 g vs. 1.2 ± 0.29 g, p = 0.002), accompanied with higher adipocyte diameters (80 ± 1.7 µm vs. 61 ± 4.7 µm, p < 0.01). These differences were not observed in the intra-abdominal fat deposit. The number of stroma cells in both adipose tissue territories was increased in t-PA−/− as compared to WT mice (2.0 ± 0.13 vs. 1.5 ± 0.10 p = 0.02 and 3.0 ± 0.17 vs 1.6 ± 0.17, p = 0.0001, stroma cells/ adipocytes in sc and intra-abdominal tissue, respectively), partly as a result of an increased number of endothelial cells (192 ± 9 vs. 154 ± 18 p = 0.06 and 108 ± 13 vs. 69 ± 8 p = 0.04 CD31 stained/adipocyte area). In contrast the weight gain and adipose tissue development in u-PA−/− mice was not different from that in WT mice. These data suggest that t-PA but not u-PA plays a role in adipose tissue development.
Keywords: Obesity; fibrinolysis; t-PA; u-PA; mice